2020
DOI: 10.18433/jpps31003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of effectiveness and safety outcomes of abiraterone versus enzalutamide in patients with metastatic castration-resistant prostate cancer: a systematic review and meta-analysis

Abstract: Purpose: To compare the effectiveness and safety between abiraterone and enzalutamide in the treatment of patients with metastatic castration-resistant prostate cancer (mCRPC). Methods: We systematically searched for relevant articles from PubMed, Cochrane, Embase from their inception through November 4, 2019. Available articles from conferences were searched. The endpoints were prostate-specific antigen (PSA) response, overall survival (OS), progression-free survival (PFS), number of patients with any adverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…However, some studies had different findings. A more recent meta-analysis of 15 cohort studies involving 3546 participants showed that the PSA response rate—but not overall survival—was significantly greater in the enzalutamide group than in the abiraterone group ( Wang et al, 2020 ). In an earlier study, Zhang et al (2017) announced that indirect comparisons between abiraterone and enzalutamide in mCRPC showed no statistically significant difference in overall survival in pre-chemotherapy and post-chemotherapy settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, some studies had different findings. A more recent meta-analysis of 15 cohort studies involving 3546 participants showed that the PSA response rate—but not overall survival—was significantly greater in the enzalutamide group than in the abiraterone group ( Wang et al, 2020 ). In an earlier study, Zhang et al (2017) announced that indirect comparisons between abiraterone and enzalutamide in mCRPC showed no statistically significant difference in overall survival in pre-chemotherapy and post-chemotherapy settings.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and a network meta-analysis of the treatments for chemotherapy-naive patients revealed that enzalutamide was superior to abiraterone/prednisone and sipuleucel-T with regard to radiographic progression-free survival ( McCool et al, 2018 ). Another meta-analysis that focused on the effectiveness and safety outcomes of abiraterone vs. enzalutamide in patients with mCRPC demonstrated that enzalutamide was associated with a higher prostate-specific antigen (PSA) response rate than abiraterone in patients with mCRPC, and no significant difference was found between the two groups with regard to overall adverse effects ( Wang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the US reference values allow for the interpretation of cognitive impairment and fatigue in the advanced prostate cancer clinical trials compared to the national norms of cognitive impairment and fatigue. This is important for prostate cancer, as cognitive impairment and fatigue are common treatmentrelated impacts [32][33][34] and the specific interaction between cognitive impairment and fatigue has not been thoroughly explored. The results of the crosstabulation of the PROMIS Fatigue-SF4a and Neuro-QoL 2.0 Cognitive Function Short Form mean reference values indicate that within the general population a large percentage of the raked male population (median age of 70 years) have above average fatigue and/or below average cognitive function (227 [26%]).…”
Section: Reference Scores By Questionnairementioning
confidence: 99%
“…Researchers can take these results into account when they evaluate fatigue and cognitive impairment in patients with advanced prostate cancer. Some evidence suggests that the high rates of cognitive impairment and fatigue observed in males in advanced prostate cancer trials may in part result from their advanced age (not necessarily solely resulting from the cancer itself or the treatment [32][33][34]). Finally, the reference values can help define HRQoL cut-off scores for certain subgroups in advanced prostate cancer clinical trial populations such as mHSPC and mCRPC.…”
Section: Reference Scores By Questionnairementioning
confidence: 99%
“…In a recent retrospective study, comparing them in the first line of mCRPC showed that ENZA had better mOS compared to AA (HR 0.90, 95% CI 0.85, 0.96; mOS, 31.7 months for AA and 34.2 months for ENZA) [10]. A metaanalysis by Wang et al [11] concluded that ENZA was associated with a higher PSA response rate compared to AA in patients with mCRPC, and no significant difference was found in terms of toxicity profiles. These anti-androgens are generally preferred instead of docetaxel in geriatric patients who have numerous comorbidities.…”
Section: Introductionmentioning
confidence: 99%